PENERAPAN MEANINGFUL LEARNING DALAM PEMBELAJARAN SEJARAH - Rina Nuriana; Iis Husnul Hotimah (Universitas Negeri Gorontalo, 2023)
The writing of this paper aims to determine the application of meaningful learning in history learning. As for the preparation, the author uses the literature method, both book sources and journals found on the internet. In addition, the purpose of the preparation of this work is to explain the importance of meaningful learning in the learning process in schools, besides that the author also applies it in the design of history learning in schools. Seeing that history learning is one of the learning that contains noble values in it, so that by using this meaningful learning strategy students not only get limited knowledge, but the learning results can be applied in solving problems, answering questions, and producing good attitudes and characters of students. Based on the discussion that has been done by the author that Ausubel's learning theory is one of the many learning theories that are the basis for cooperative learning. Ausubel's learning theory is suitable for use in history learning, because the learning process will be more meaningful if students are able to connect the knowledge they have with learning material in the classroom.